2017
DOI: 10.1111/bjh.14631
|View full text |Cite
|
Sign up to set email alerts
|

Early mortality and complications in hospitalized adult Californians with acute myeloid leukaemia

Abstract: SUMMARY Few studies have evaluated the impact of complications, sociodemographic and clinical factors on early mortality (death ≤ 60 days from diagnosis) in acute myeloid leukaemia (AML) patients. Using data from the California Cancer Registry linked to hospital discharge records from 1999–2012, we identified patients aged ≥ 15 years with AML who received inpatient treatment (N=6359). Multivariate logistic regression analyses were used to assess the association of complications with early mortality, adjusting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 53 publications
4
45
2
Order By: Relevance
“…Hepatic parenchymal infiltration in acute myelogenous leukaemia (AML) has rarely been reported despite AML being one of the most common acute leukaemias 1. Previous literature suggested that if patients with AML develop acute liver failure, mortality rates are 1.9 times higher 2. We report a case of liver infiltration by AML resulting in acute liver failure which is uncommon to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 85%
“…Hepatic parenchymal infiltration in acute myelogenous leukaemia (AML) has rarely been reported despite AML being one of the most common acute leukaemias 1. Previous literature suggested that if patients with AML develop acute liver failure, mortality rates are 1.9 times higher 2. We report a case of liver infiltration by AML resulting in acute liver failure which is uncommon to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 85%
“…However, differences in outcomes of patients treated in pediatric versus adult trials are more pronounced for adolescent patients with ALL than for patients with AML even when chemotherapy intensity is generally higher in pediatric AML protocols than in adult protocols, and HSCT is given more restrictively (risk adapted) than that given for adults. AYA‐specific approaches can be influenced further by referring these patients to centers experienced in managing leukemia or centers participating in clinical trials for children or adults . Cooperation between pediatric and adult study groups is of utmost importance.…”
Section: Treatment In Pediatric Versus Adult Trialsmentioning
confidence: 99%
“…AYA-specific approaches can be influenced further by referring these patients to centers experienced in managing leukemia or centers participating in clinical trials for children or adults. 20,71 Cooperation between pediatric and adult study groups is of utmost importance. AYA patients need to be enrolled in clinical trials, and cross-study analyses comparing strategies for pediatric and adult patients are required.…”
Section: Treatment In Pediatric Versus Adult Trialsmentioning
confidence: 99%
“…We previously observed that race/ethnicity, neighborhood socioeconomic status, marital status and location of care impacted early mortality in AML patients. 9 .…”
Section: Introductionmentioning
confidence: 99%
“…9 In this present study, we examine differences in sociodemographic and clinical characteristics of AML patients treated at NCI versus non-NCI-CCs. We also evaluate the impact of hospital type on early mortality while controlling for these differences and examine whether complications during initial therapy by location of care impact early mortality.…”
Section: Introductionmentioning
confidence: 99%